ChemInform Abstract: Sodium Paramolybdate Revisited. Issue 44 (13th October 2016) - Srinivasan, Bikshandarkoil R.; Morajkar, Sudesh M.
Abstract: The heptamolybdate (NH4 )6 [Mo7 O24 ]·4H2 O (I) is prepared by dissolving H2 MoO4 ·H2 O in excess NH3 followed by solvent evaporation (≈100% yield).